2022
DOI: 10.3390/nu14193977
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Months of Time-Restricted Feeding Improves Cognition and Alters Microbiome Composition Independent of Macronutrient Composition

Abstract: Declining health, gut dysbiosis, and cognitive impairments are hallmarks of advanced age. While caloric restriction is known to robustly extend the healthspan and alter gut microbiome composition, it is difficult maintain. Time-restricted feeding or changes in dietary macronutrient composition could be feasible alternatives for enhancing late life cognitive and physical health that are easier to comply with for extended periods of time. To investigate this possibility, 8-month-old rats were placed on time-rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Due to this time-restricted feeding, both groups experienced intermittent fasting. Intermittent fasting, even with a normal control diet, can affect gene expression in the brain (Castrogiovanni et al, 2018;Spezani et al, 2020;Ng et al, 2022), confer neuroprotection (Halagappa et al, 2007;Mattson et al, 2017;Anton et al, 2018), and alter the gut microbiome (Hernandez et al, 2022a;Hernandez et al, 2022b). Because all rats received intermittent fasting, it is possible that potential diet by age interactions were less than would have been observed with free feeding animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to this time-restricted feeding, both groups experienced intermittent fasting. Intermittent fasting, even with a normal control diet, can affect gene expression in the brain (Castrogiovanni et al, 2018;Spezani et al, 2020;Ng et al, 2022), confer neuroprotection (Halagappa et al, 2007;Mattson et al, 2017;Anton et al, 2018), and alter the gut microbiome (Hernandez et al, 2022a;Hernandez et al, 2022b). Because all rats received intermittent fasting, it is possible that potential diet by age interactions were less than would have been observed with free feeding animals.…”
Section: Discussionmentioning
confidence: 99%
“…Because all rats received intermittent fasting, it is possible that potential diet by age interactions were less than would have been observed with free feeding animals. In fact, rats the receive ad libitum feeding from middle-to old-age have worse cognitive performance compared to both ketogenic and control-fed rats that received intermittent fasting during the same time period (Hernandez et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhythmic SFB attachment drives diurnal rhythms in the expression and activation of signal transducer and activator of transcription 3 (STAT3), a key regulator for immune response, which modulates the rhythms of antimicrobial proteins, including regenerating islet-derived protein 3𝛾 (REG3G), lipocalin-2 (LCN2) and S100A8, and thus stimulates intestinal innate immunity. [73] Other studies also showed that TRF can adjust the gut microbiota, [74][75][76] however the relationship with circadian rhythms is currently unknown. Although increasing evidence suggests that the benefits of TRF are dependent on a functional circadian clock, a previous study showed that TRF can still alleviate metabolic stress and prevent metabolic disorders in mice lacking a circadian clock.…”
Section: Time-restricted Feedingmentioning
confidence: 99%
“…TRF is also beneficial in middle‐aged flies, as it prevents age‐dependent body weight gain and leads to better consolidated nighttime sleep [31]. This extends to other aging‐related dysfunction, as TRF prevents age‐associated cognitive decline in rats [43]. Obesity and weight are risk factors for other cardiometabolic and age‐associated diseases, and TRF ameliorates both along with improving circadian rhythmicity, highlighting its broad therapeutic potential for cardiometabolic diseases.…”
Section: Circadian Rhythms and Trf/trementioning
confidence: 99%